Effect of Subclinical Hypothyroidism on Serum Lipid Profile - Nikhil Rajendra Arve , Samir Sahu, JB Kanwar, Subhashree Ray (International Journal of Advanced Science and Technology, 2020)
Hypothyroidism both overt and subclinical is a risk factor for altered lipid metabolism, hypercoagulable stateand inflammation which is low gradeas established by many studies. Previous studies are suggestive of increase in serum total cholesterol levels and very low density lipoproteins and decrease in HDL cholesterol. Thyroid hormone has various metabolic effects including its effect on carbohydrate, proteins and lipids. The authors evaluated the alteration in lipid parameters in subclinical hypothyroidism. Twenty controls, twenty subclinical hypothyroid patients on the basis of T3, T4 and TSH levels in serum were included in this study. Subclinical hypothyroidism was associated with raised LDL, hypercholesterolemia, hypertriglyceridemia and decreased levels of HDL. Significant association was found between increase in serum TSH level with raised total cholesterol, Triglycerides, LDL and decreased HDL level. Due to adverse effect of subclinical hypothyroidism on lipid metabolism which may contribute to increased risk of cardiovascular disease and metabolic syndrome, screening and management of subclinical hypothyroidism may be warranted.